T-shirt factory - Beams T. (Firm) (New York Collins Design, 2007)
Features designs selected by Beams T, a hugely popular fashion retail chain and manufacturer in Japan devoted to T-shirts. Beams T regards the T-shirt as a canvas for new ideas in art and design, and in each year invites artists from around the world to create designs for their T-shirts, 300 of which are featured here.
Keywords: T-shirts -- Design -- Catalogs